Integrasi Etika Bisnis Islam dan Digital Marketing terhadap Loyalitas Pelanggan dengan Kepercayaan dan Kepuasan sebagai Variabel Intervening - Rahimi, Faishal; Akbar, Zulfikri Akramul; Akbar, Ilham (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation in the halal business requires harmonizing modern marketing technologies with Islamic ethical principles. This study examines the influence of Islamic Business Ethics and Digital Marketing on Customer Loyalty, mediated by Trust and Customer Satisfaction. Using a quantitative explanatory approach, data were collected from 200 Indonesian users of digital-based halal products and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings reveal that all hypotheses (H₁–H₈) are significantly supported (p < 0.05). Islamic Business Ethics positively affects Trust (β=0.372) and Satisfaction (β=0.298), while Digital Marketing significantly impacts Trust (β=0.421) and Satisfaction (β=0.355). Trust enhances both Satisfaction (β=0.294) and Loyalty (β=0.318), whereas Satisfaction strongly drives Loyalty (β=0.367). Mediation analysis confirms that Trust and Satisfaction jointly mediate the relationships between Islamic Business Ethics, Digital Marketing, and Loyalty. The R² value of 0.734 indicates that 73.4% of Loyalty variance is explained by these constructs, with a GoF value of 0.706, signifying an excellent model fit. The study concludes that incorporating shidq (honesty), amanah (trustworthiness), and ‘adl (justice) into digital marketing strengthens customer trust and loyalty in the digital era. Islamic ethics thus serve not only as moral guidance but also as strategic differentiators that foster spiritual and emotional connections between customers and halal brands. This research contributes empirically to Islamic marketing literature and offers practical insights for firms developing digital strategies rooted in Islamic values and sustainable customer relationships